The growth and yield of Capsicum annuum L. variety Gada F1 on NPK 16:16:16 fertilizer - Zerika Regina Ramadhan Fitri; Susilawati Susilawati (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2025)
Red chili was one of the most strategic vegetable commodities because the market demand was high every day. Efforts to increase chili productivity were needed so that chili prices were stable and market demand was met. The research aimed to determine the growth and yield of the red chili Gada F1 variety against NPK 16:16:16 fertilizer. This research uses the Randomized Block Design (RBD) method, consisting of 4 treatment levels and 3 replications. P0 = control, P1 = NPK fertilizer 2.5 g/polybag, P2 = NPK fertilizer 5 g/polybag, and P3 = NPK fertilizer 7.5 g/polybag. The application of NPK 16:16:16 fertilizer to the growing medium significantly influenced several growth and yield parameters, including the number of leaves, crown diameter, leaf greenness, fruit weight, number of fruits, fruit length, and fruit diameter. In contrast, it had no statistically significant effect on plant height, flowering time, number of branches, root fresh weight, crown fresh weight, root dry weight, or crown dry weight. Among the treatments, the application rate of 7.5 g/polybag (P3) yielded the most favorable results across the majority of measured parameters. Accordingly, an NPK 16:16:16 dosage of 7.5 g/polybag was recommended for the cultivation of the red chili (Capsicum annuum L.) variety Gada F1.